First report of Apple stem grooving virus and Apple scar skin viroid infecting low‐chilling apple varieties in India. (26th April 2022) - Rani, A.; Lohan, S.; Srivastava, A.; Kaushik, N. K.; Noorani, Md. S.; Walia, Y.; Dhir, S.
Abstract: Low‐chilling apple varieties are gaining attention in plain regions with high temperatures but viruses are also adapting to these conditions. In this report, we have characterized Apple stem grooving virus and Apple scar skin viroid from the low‐chilling apple samples collected from district District Mandla of Madhya Pradesh and Kangra of Himachal Pradesh, India. To our knowledge, this is the first report of ASGV and ASSVd infecting low‐chilling apple varieties in India.